Réponses

2014-04-27T14:28:55+02:00
Bonjour,
1) B= (6x-7) (3-2x)
       = 6x*3 - 6x *2x- 7 *3 + 7* 2x
       =  
18x - 12x² - 21 + 14x
       =    
-12x² + 32x-21
2) x= 0
   
-12*0² + 32*0-21
=   0 + (-21) 
=  -21

 2) x= 1
-12*1²+32*1-21
-12+32-21
= 1
Si tu as des questions n'hésite pas
Meilleure réponse !
2014-04-27T14:32:39+02:00
* = multiplier
1. B= 6x * 3 - 6x * 2x -7 * 3 + 7 * 2x
    B=  18x - 12x² - 21 + 14x
   B= 32x - 12x² -21

2. Pour x = 0
32 x 0 - 12*0² -21
= -21

Pour x = 1
32*1 - 12*1² - 21
= 32-12-21
= -1

Voilà :)